PENGARUH TAYANGAN TALKSHOW “INDONESIA LAWYERS CLUB” TERHADAP PENDIDIKAN POLITIK MAHASISWA - CHAIRIL ANSYORIE; AZHAR MARWAN; KHAIRIL BULDANI (UNIVED PRESS, Universitas Dehasen Bengkulu, 2019)
This study contains the effect of the Indonesian lawyers club talk showon student political education. This research uses purposivesampling with the criteria of Communication Studies University of Bengkulu Universityclass of 2015-2017 who watched the talk show